Reputation Matters : Spillover Effects in the Enforcement of US SPS Measures - Jouanjean, Marie-Agnes (2012)
This paper uses a novel dataset on United States food import refusals to show that reputation is an important factor in the enforcement of sanitary and phytosanitary measures. The strongest reputation effect comes from a country's own history of compliance in relation to a particular product. The odds of at least one import refusal in the current year increase by more than 300 percent if there was a refusal in the preceding year, after controlling for other factors. However, the data are also suggestive of the existence of two sets of spillovers. First, import refusals are less likely if there is an established history of compliance in relation to other goods in the same sector. Second, an established history of compliance in relation to the same product by neighboring countries also helps reduce the number of import refusals. These findings have important policy implications for exporters of agricultural products, especially in middle-income countries. In particular, they highlight the importance of a comprehensive approach to upgrading standards systems, focusing on sectors rather than individual products, as well as the possible benefits that can come from regional cooperation in building sanitary and phytosanitary compliance capacity.